DESIGN OF DECISION SUPPORT SYSTEM ANALYSIS MODEL FOR PRODUCTION RESULT ASSESSMENT IN AUTOMOTIVE COMPANIES IN EAST JAVA - BILHAN GAMALIEL HARTANTO; GALI PRIBADI (CV KULTURA DIGITAL MEDIA, 2021)
Effective decision making requires a Decision Support System (DSS) that integrates data, automated simulation models, and interactive visualization. The DSS is used to improve the effectiveness of machine operation scheduling, identify lines that require overtime, and develop action plans for lines that do not meet production targets. The use of Macro VB Excel accelerates data query and root cause analysis through fishbone and FMEA, increasing the efficiency of analysis time by 3.5 hours faster and requiring an additional 7.4 shifts of overtime to achieve the production target of 20,593 pcs. In the production meeting, four action plans were proposed including the creation of SOPs to minimize machine adjustments, routine overtime settings, different operation settings for materials from suppliers, and standardization of parameters for each production process.